Dwelling and Departure: Beginning Disputes between Arendt and Heidegger - Burton, Adi; Weber, Barbara (Text Matters: A Journal of Literature, Theory and Culture, 2024)
In “Letter on Humanism,” Martin Heidegger juxtaposes the notion of homelessness (Heimlosigkeit) with home-coming (Heimholung), i.e. the reawakening to our original relationship to Being. This focus on dwelling in Being represents an interesting modification from his earlier study of “incipience” (Anfang), which emphasizes departure. We follow the critique of this shift in thinking in Hannah Arendt’s work, beginning with a short allegory titled “Heidegger the Fox” (1953). We suggest that reading this allegory in the light of Arendt’s decades-long debate with Heidegger illuminates the tense relationship between dwelling and incipience (or in her terms, “natality”). Though we do not attempt a complete analysis of Heidegger and Arendt’s works here, we aim to draw out specific movements of their thinking. We suggest that Arendt’s concept of natality, which, though partly influenced by Heidegger, ultimately challenges the authenticity of Heidegger’s solitary, silent thinker who dwells in the House of Being. In the back and forth between their thinking an unresolvable tension between dwelling and departure arises as the existential fissure.